PENGARUH MOTIVASI KERJA, REMUNERASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN A PASURUAN - jurnalmap map; Nunik Wahyuni; C. Sri Hartati; Ruddy Winarko (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
The purpose of this research is to describe the Influence of Motivation, Remuneration and Job Satisfaction on Employee Performance to Employees of Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean A Pasuruan. To know the significant influence of Motivation, Remuneration and Job Satisfaction on Employee Performance partially or simultaneously and to know among Motivation, Remuneration and Job satisfaction factors that have dominant influence to Employee Performance. The Population in this research were all employees of Executives Office of Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean A Pasuruan 68 people. The results descriptive analysis show that Motivation mean 4.42, mean remuneration 4.18, job satisfaction mean 4.23 and employee performance with mean of 4.37 already in very high condition range 268 scale. Motivation, Remuneration and Job Satisfaction partially or simultaneously have a significant effect on Employee Performance. Of the three variables that are used as Employee Performance predictor, the remuneration variable is identified as the strongest variable affecting Employee Performance compared to the other two variables, namely Motivation, and Job Satisfaction.Keywords: motivation, remuneration, job satisfaction, employee performance